Identification Of Migratory Birds And Their Spesific Characteristics Of Habitat In The Salt Water Lake Of Gili Meno, North Lombok Distric - Diah Purwitasari; Luh Gde Sri Astiti; Supriadi Supriadi (Sunan Kalijaga State Islamic University & Society for Indonesian Biodiversity, 2014)
The aim of this research was to identify the species of migratory birds in the ecosystem of salt water lake of Gili Meno and their specific characteristics of habitat. Data collection for birds, mangrove and fish species has been carried out in September and October 2013. In this study, a Shannon-Wiener Diversity Index and Importance Value Index (IVI) of mangrove vegetation were calculated to identify carrying capacity of mangrove population in the form of specific habitat in salt water lake of Gili Meno. This research has identified 17 species of birds which are divided into 5 families: Scolopacidae, Charadriidae, Ardeidae, Meropidae and Alcedinidae. Moreover, 3 species of mangrove were discovered that are A. marina, A. lanata and E. Agallocha, as well as one species of fish (Mujair fish/O. mossambicus). N. Nycticorax and B. Striatus were well-known to have higher population than other bird species. The Diversity Index showed that mangrove vegetation in the ecosystem of salt water lake of Gili Meno has a low species diversity (0.565). This is due to higher dominance of one species than the others. What is more, the IVI of A. marina demonstrated a fairly significant value compared to that of other species (189,01). Mangrove vegetation which surrounds the ecosystem of salt water lake of Gili Meno has formed a unique habitat and and an ideal stopover site for migratory birds. The ecosystem not only provides shelters from predators but also supplies for various abundant feeding sources. The lake it self is rather shallow and muddy around the shore which gives advantages for the migratory birds to obtain plenty small fish from the lake.